A torrefaction of Sida hermaphrodita to improve fuel properties. Advanced analysis of torrefied products. (October 2019) - Szwaja, Stanisław; Magdziarz, Aneta; Zajemska, Monika; Poskart, Anna
Abstract: Sida hermaphrodita is one of the energy crops with high potential for energy conversion technologies. In this study the torrefaction of Sida hermaphrodita was carried out at the specially constructed test bench simulating industrial like process operating conditions. The torrefaction temperature was in the range from 250 to 350 °C. The obtained solid products (biochars) were characterized in terms of its proximate and ultimate properties. The chemical analysis of liquid phase was also performed. The combustion process of obtained biochars was examined by Simultaneous Thermal Analysis (STA) through dynamic runs at 10 °C/min heating rate from RT to 700 °C. The structural changes during the torrefaction were studied using scanning electron microscope technique. The fibre analysis was performed to determine structural composition (the content of hemicellulose, cellulose and lignin). Results from analyses significantly contributed to extending databases in the field of plant torrefaction. The results confirmed positive features of obtained biochars comparing to raw biomass material. It was concluded, that the optimal process temperature for Sida hermaphrodita should not exceed 400 °C. Additionally, the mineral matter was investigated using X-ray Fluorescence (XRF) to study the influence of torrefaction on chemical composition of the ash. Only some differences in ash compounds were observed. Highlights: Sida Hermaphrodita torrefaction process were conducted at specified temperatures. Increasing process temperature leads to enhance energy properties of obtained biochar. The fibre and structural analyses confirmed the changes in morphology structure. Condensates of torrefaction contained high amount of organics.